The relationship between service quality (SERVQUAL) and customer satisfaction towards customer re-patronage intentions in Johor Bahru tourism / Nur Afifah Johari - Johari, Nur Afifah (2015)
Malaysia is one of Southeast Asia’s top travel destinations. Malaysia tourism is important sector of the Malaysian economy. Unfortunately, many incidents happened in 2014 that affected Malaysia tourism sector, but the number of tourists increased in 2014 as compared to previous year. This study is to determine the relationship between SERVQUAL and Customer Satisfaction towards Customer Re-Patronage Intention in Johor Bahru tourism. The three main independent variables will describe in the literature and research framework. Data was collected through survey questionnaires. A convenience sampling under non-probability sampling was chosen. The researcher employed descriptive analysis to provide accurate and valid representation of the factors or variables that pertain or are relevant to the research question and mean has been used in this study. Based on data obtained, the SERVQUAL and customer satisfaction a significant towards customer re-patronage intention. SERVQUAL has a strong relationship with customer re-patronage and assurance are more impact on customer under SERVQUAL.